\(\left(5\cdot x+7\right):2=16\) \(128-3\cdot\left(x-4\right)=23\)
\(\left(5\cdot x+7\right)=16\cdot2\) \(3\cdot\left(x-4\right)=128-23\) \([\left(4\cdot x+28\right)\cdot3+55]:5=35\)
\(\left(5\cdot x+7\right)=32\) \(3\cdot\left(x-4\right)=105\) \([\left(4\cdot x+28\right)\cdot3+55]=35\cdot5\)
\(5\cdot x=32-7\) \(x-4=105:3\) \([\left(4\cdot x+28\right)\cdot3+55]=175\)
\(5\cdot x=25\) \(x-4=35\) \(\left(4\cdot x+28\right)\cdot3=175-55\)
\(x=25:5\) \(x=35+4\) \(\left(4\cdot x+28\right)\cdot3=120\)
\(x=5\) \(x=39\) \(\left(4\cdot x+28\right)=120:3\)
\((4\cdot x+28)=40\)
\(4\cdot x=40-28\)
\(4\cdot x=12\)
\(x=12:4\)
\(x=3\)
Chúc bạn hok tốt !
a) 5x X+7=16x2 b)3x(X-4)=128-23 c)(4x X +28 ) x 3 + 55 = 35 x 5
5xX+7=32 3x(X-4)=105 (4x X + 28) x3 +55 =175
5xX=32-7 X-4 = 105 : 3 (4x X + 28 ) x3 = 175 -55
5xX=25 X-4 = 35 (4x X + 28 ) x3 = 120
X=25:5 X = 35 + 4 4x X + 28 = 120 : 3=40
X=5 X = 39 X = (40-28):4=3